Tiling arbitrarily nested loops by means of the transitive closure of dependence graphs - Bielecki, Włodzimierz; Pałkowski, Marek (Zielona Góra: Uniwersytet Zielonogórski)
A novel approach to generation of tiled code for arbitrarily nested loops is presented. It is derived via a combination of the polyhedral and iteration space slicing frameworks. Instead of program transformations represented by a set of affine functions, one for each statement, it uses the transitive closure of a loop nest dependence graph to carry out corrections of original rectangular tiles so that all dependences of the original loop nest are preserved under the lexicographic order of target tiles.
Keywords: tiling; transitive closure; source-to-source compiler; polyhedral model; iteration space slicing